Procesos de aprendizaje y rendimiento académico en el área de Matemática en la carrera de Ingeniería Agroindustrial de la Universidad Técnica de Cotopaxi en el año 2012. Diseño de un módulo alternativo de estrategias y técnicas de aprendizaje para el docente. - López Bonilla, Vinicio Xavier (2014)
This research aims to improve the teaching-learning process in college students using strategies and techniques grounded in changing mindsets learning and cognitive structures of educators and learners to develop critical logical thinking. It is based on the analysis of methodological factors in academic performance of students in the career of Agroindustrial Engineering at the Technical University of Cotopaxi in the Academic Unit of Agricultural Sciences and Natural Resources , the work begins with a detailed description of the complexity of the teaching mathematics is based on teaching some principles that characterize higher education and subsequently methodological strategies and techniques for teaching this lecture is analyzed. The experimental research is descriptive, through induction, deduction, analysis and synthesis under a qualitative perspective. Data were collected through classroom observation and survey students and teachers of the race Agroindustrial Engineering. The theoretical framework discusses a study through the analysis and interpretation of research results and based on fundamental aspects of different authors justify allowing some aspects and point out methodological strategies and techniques that meet the educational and pedagogical principles for efficient development of the learning of mathematics at a higher level .